Spotlight on Japanese physicians: An exploration of their professional experiences elicited by means of narrative facilitators. - Stiefel, F.; Stiefel, Fa.; Terui, T.; Machino, T.; Ishitani, K.; Bourquin, C. (Work, 2019)
BACKGROUND: While investigation of physicians' work experience is often limited to issues of satisfaction or burnout, a broader view of their experiences is lacking. OBJECTIVE: To explore professional experiences, we asked Japanese physicians (N = 18, 12 men and 6 women) of a general hospital to react to so-called "narrative facilitators". METHODS: The narrative facilitators – inspired by clinical psychology, visual sociology and purpose-designed techniques – oriented physicians' narratives towards clinical practise, relationship with peers and context. Transcribed interviews were subject to thematic analysis. RESULTS: The thematic analysis of participants' narratives revealed a lonely physician with a tough job, torn between the ideal of patient-centred care and a clinical reality, which limits these aspirations. Patients emerged as anxious and burdensome consumers of medicine. Feeling neither supported by peers nor the institution, physicians also perceived the society as somewhat negligent, delegating its problem to medicine. Communication difficulties, with patients and peers, and the absence of joyful aspects of the profession constituted fundamental elements of their narratives. CONCLUSIONS: Comprehensive investigation of physicians' lived professional experience could become a key to conceive ways to support them.